2007
DOI: 10.1080/09243450601058675
|View full text |Cite
|
Sign up to set email alerts
|

The effect of class size on the teaching of pupils aged 7 – 11 years

Abstract: There is still little consensus on whether and how teaching is affected by small and large classes, especially in the case of students in the later primary years. This study investigated effects of class size on teaching of pupils aged 7-11 years. We used a multi-method approach, integrating qualitative information from teachers' end-of-year accounts and data from case studies with quantitative information from systematic observations. Results showed that there was more individual attention in smaller classes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 21 publications
4
54
0
3
Order By: Relevance
“…In line with this assumption some authors suggest that groups of students should be left alone working for considerable amounts of time as frequent intervention might disturb the learning process (e.g., Cohen 1994). Other studies, however, found that students benefit in classrooms with a lot of individual attention (Blatchford et al 2007;Brühwiler and Blatchford 2007). Although it is not known to what extent students should work independently, it is now generally agreed that students at least need some support and guidance during the learning process and that minimal guidance does not work (e.g., Kirschner et al 2006).…”
Section: Scaffolding Task Effort and Appreciation Of Supportmentioning
confidence: 98%
“…In line with this assumption some authors suggest that groups of students should be left alone working for considerable amounts of time as frequent intervention might disturb the learning process (e.g., Cohen 1994). Other studies, however, found that students benefit in classrooms with a lot of individual attention (Blatchford et al 2007;Brühwiler and Blatchford 2007). Although it is not known to what extent students should work independently, it is now generally agreed that students at least need some support and guidance during the learning process and that minimal guidance does not work (e.g., Kirschner et al 2006).…”
Section: Scaffolding Task Effort and Appreciation Of Supportmentioning
confidence: 98%
“…Teachers need these skills, especially if they work with large classes. Due to the more passive role of pupils in larger classes, teachers have to engage in a whole class teaching (Blatchford, Russell, Bassett, Brown & Martin, 2007). Therefore, teachers have to cover all types of contact, including different procedures and routines.…”
Section: Processes At Micro Levelmentioning
confidence: 99%
“…(T6). Blatchford, Russell, Bassett, Brown & Martin (2007) also noted the efficiency of working in small classes, and suggested, it made it easier to detect problems of every student, to identify their individual goals and give them feedback.…”
Section: Teachers' Professional Development In the Context Of Decisiomentioning
confidence: 99%
“…A year later the study was extended to Year 4 to Year 6 students aged 7-11 years from over 200 schools (Blatchford et al, 2007). The researchers found more individualised teaching in smaller classes but, in contrast to the previous study, teachers used more whole class teaching in both larger and smaller classes.…”
Section: United Kingdommentioning
confidence: 76%
“…Teachers must be provided with learning opportunities that enable them to understand and use pedagogies that promote increased academic performance in small classes (Hattie, 2009). This might include a more differentiated learning environment that accommodates a diversity of student interests and gloBalising tHe class size deBate ability, the use of open-ended investigation techniques, an emphasis on collaborative group work, remedial assistance, and increased interactivity that discourages student passivity and includes the development of student help-seeking behaviours (Blatchford et al, 2007).…”
Section: Resultsmentioning
confidence: 99%